Business resilience a dynamic capability to overcome extreme adversity (2019)
This article delimits the business resilience concept making however a direct association with dynamic capabilities, and reviews 3 crucial moments a turbulent company endures and has to overcome in order to be resilient. It is being presented in the form of a case study of the Colombian construction company AIA with a qualitative methodology. With the above, I want to share with the scientific community the findings that will explain how theories of dynamic capability and resilience could be a strategy for business recovery. The final results reflect what an organization must not do and thus should do in order to use this powerful dynamic capability better known as resilience to stay in or get to a number one spot in the market. © 2019.Este artículo delimita el concepto de resiliencia empresarial estableciendo una asociación directa con las capacidades dinámicas, y revisa tres momentos cruciales que una empresa turbulenta padece y debe superar con el fin de ser resiliente. Se presenta bajo la forma de un estudio de caso de la empresa constructora colombiana AIA con una metodología cualitativa. Con lo anterior, deseo compartir con la comunidad científica los hallazgos que explicarán cómo las teorías de capacidad dinámica y resiliencia podrían ser una estrategia para la recuperación empresarial. Los resultados finales reflejan lo que una organización no debe hacer y, por lo tanto, debe hacer para utilizar esta poderosa capacidad dinámica, mejor conocida como resiliencia, para permanecer o llegar al puesto número uno en el mercado. © 2019.